Constituting the occupation: preventive detention and permanent emergency in Kashmir. Issue 3 (2nd September 2017) - Duschinski, Haley; Ghosh, Shrimoyee Nandini
ABSTRACT: This article analyzes Indian occupation of Kashmir as a legal, social, and spatial process of asserting power through borders and jurisdictional claims, produced and reproduced through constitutional processes and legal institutions that have enacted generalized notions of emergency and crisis. We argue that the distinctive socio-spatial power structures established between India and Kashmir in a provisional capacity amidst war and partition at the time of independence have been legitimized through rights regimes established through the constitutional structure and institutionalized through laws, executive orders, and the judicial system. We examine how India's legal incorporation of Kashmir was embedded in the constitutional drafting process and the extension of fundamental rights to the region through presidential orders, and how this legal incorporation became sedimented through the work of the courts across time. Building on Ranabir Samaddar's discussion of "colonial constitutionalism, " we consider "occupational constitutionalism" as a form of foreign dominance and control produced through the annexation of part of Kashmir's territory and its legal sovereignty to India in the aftermath of independence and reproduced through a series of legal mechanisms and processes across time that institute a state of emergency and permanent crisis in Kashmir.